AN EXPLORATION OF DIFFICULT ENGLISH CONSONANTS FOR PASHTO L1 LEARNERS AT BS LEVEL IN COLLEGES OF DISTRICT BAJAUR, KP (Contemporary Journal of Social Science Review, 2025)
This study examined the resemblances and differences between Pashto and English consonants and pointed out the difficulties faced by Pashto L1 learners in pronouncing certain English consonants at various word positions. This study also explained the acquisition of certain English consonants posed difficulty to Pashto L1 learners. The target population of the study was 75 male and 25 female BS students; their age ranged between 16-22 years from the Government Degree Colleges in District Bajour (Ex. FATA). A survey was conducted through a test and class room observation. Data was collected by applying a mixed-methods approach. The most difficult English consonants were identified and analyzed by using Praat software. It was found that Pashto speaking students have difficulties in the articulation of English aspirated sounds like ([ph], [th], and [kh]) and some fricatives like /f/, /v/, and dental like /θ/, /ð/. As Pashto language has retroflex, so some English sounds /d/, /t/ and /ŋ/ were articulated with retroflex ending. It aimed to enhance the pronunciation skills of Pashto learners and address the challenges in pronouncing English consonants. Thus, the study provides insights into effective teaching approaches for improving the pronunciation skills of Pashto learners in order to articulate English consonants accurately.